The Effect of the Job Demands-Resources Model on Innovative Work Behavior in Digital Infrastructure Organizations - Tommi Tirtawiguna; Aryana Satrya (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation has significantly reshaped public sector operations, requiring civil servants to continuously adapt to technological change while maintaining service effectiveness and innovation. This study aims to examine the effects of job demands and job resources on innovative work behavior through the mediating roles of work engagement and coping strategies among civil servants at the Directorate General of Digital Infrastructure (DJID), Ministry of Communication and Digital, Indonesia. A quantitative explanatory approach was employed using survey data collected from 621 employees. Data were analyzed using covariance-based Structural Equation Modeling (SEM) with LISREL. The findings reveal that job demands negatively affect work engagement but positively influence innovative work behavior, indicating that employees tend to perceive digital work pressures as challenge demands. Job resources positively affect both work engagement and innovative work behavior, while work engagement positively influences innovative work behavior but negatively affects coping strategies. Coping strategies positively contribute to innovative work behavior. Furthermore, work engagement partially mediates the relationships between job demands, job resources, and innovative work behavior, while coping strategies partially mediate the relationship between work engagement and innovative work behavior. These findings highlight the importance of psychological mechanisms in sustaining innovation within digitally transforming public sector organizations.